Study on the impact of digital economy on green innovation in Anhui Province through space–time evolution - Zhuo Chen; Yuhong Shao (Engineering Reports)
Abstract In today's digital economy, green innovation has become a focal point of global attention. This paper takes Anhui province as the research subject and discusses its carbon emission level through the method of space–time evolution. Moreover, it defines the role and impact relationship of green innovation, aiming to promote the development of green innovation in Anhui. This study adopts the spatio‐temporal evolution analysis method, integrating the green innovation data and digital economy development indicators in Anhui in recent years. Moreover, in order to deeply understand the internal interrelation between green innovation and the digital economy, geographic information system (GIS) technology and statistical knowledge are used. At the same time, the data from different periods and spatial scales are compared, and the spatio‐temporal evolution between them is understood using dynamic methods. It is found that in light of the current rapid economic progress, the level of green economy innovation in Anhui province is increasing overall, but at different spatial and temporal scales, the level of green innovation is slightly affected by the digital economy. In some periods and regions, the digital economy as a whole can promote green innovation levels, but the impact of this increase varies from region to region and over time. Through the analysis of temporal and spatial evolution, it is found that the level of green innovation in Anhui Province will be affected by the local digital economy, which is not regular, but presents the characteristics of diversity and complexity. Therefore, it is crucial to comprehensively consider the regional differences and progress of the digital economy to support the economic development and environmental protection of Anhui Province. Future research can be initiated by exploring the developmental mechanisms linking green innovation levels and the mode of digital development to provide more detailed policy recommendations for the advancement of green innovation.